2003
DOI: 10.1161/01.res.0000077045.84609.9f
|View full text |Cite
|
Sign up to set email alerts
|

NFATc3 and NFATc4 Are Required for Cardiac Development and Mitochondrial Function

Abstract: Activation of the nuclear factor of activated T-cell (NFAT) family of transcription factors is associated with changes in gene expression and myocyte function in adult cardiac and skeletal muscle. However, the role of NFATs in normal embryonic heart development is not well characterized. In this report, the function of NFATc3 and NFATc4 in embryonic heart development was examined in mice with targeted disruption of both nfatc3 and nfatc4 genes. The nfatc3-/-nfatc4-/- mice demonstrate embryonic lethality after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 39 publications
3
114
0
1
Order By: Relevance
“…Cyclosporin treatment of avian embryos during heart looping results in thinning of the ventricular myocardium and heart failure evident in blood pooling and pericardial effusion. A similar phenotype was observed in mouse embryos lacking both NFATc3 and NFATc4 that die at midgestation as a result of deficiencies in cardiomyocyte proliferation and metabolism (Bushdid et al, 2003). Together, these studies support a critical role for calcineurin signaling and NFAT activation in the maturation of cardiomyoctes at E3-E4 in avian embryos and E10.5-E11.5 in mice.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Cyclosporin treatment of avian embryos during heart looping results in thinning of the ventricular myocardium and heart failure evident in blood pooling and pericardial effusion. A similar phenotype was observed in mouse embryos lacking both NFATc3 and NFATc4 that die at midgestation as a result of deficiencies in cardiomyocyte proliferation and metabolism (Bushdid et al, 2003). Together, these studies support a critical role for calcineurin signaling and NFAT activation in the maturation of cardiomyoctes at E3-E4 in avian embryos and E10.5-E11.5 in mice.…”
Section: Discussionsupporting
confidence: 67%
“…Avian embryos treated with CsA from E2 to E3 exhibit thinning of the myocardium and reduced trabeculae similar to mouse embryos lacking NFATc3 and NFATc4 (Bushdid et al, 2003). These mice were originally described as having embryonic lethal vascular patterning defects, but a subsequent study demonstrated prolonged embryonic viability with cardiomyocyte-specific restoration of NFAT function (Graef et al, 2001a;Bushdid et al, 2003). The dependence of vascular development on cardiac function also has been demonstrated in mice deficient in Ncadherin or the sodium/calcium exchanger Ncx1 (Wakimoto et al, 2000;Luo et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Disruption of this transcriptional network results in a variety of human diseases including congenital heart disease, dilated cardiomyopathy, and cardiac hypertrophy (Frey and Olson, 2003;Olson, 2004;Clark et al, 2006). Central to the regulation of these developmental processes are the cardiac transcription factors GATA4 (Watt et al, 2004), NKX2.5 (Cripps and Olson, 2002), Hand (McFadden et al, 2005), nuclear factors of activated T-cell (NFAT) c3 and c4 (Molkentin, 2000;Graef et al, 2001;Bushdid et al, 2003), Foxp4 and FOG2 (Svensson et al, 2000;Lin et al, 2004), and T-box transcription factors TBX1 and TBX5 (Plageman and Yutzey, 2005), all of which have been shown to regulate cardiomyocyte proliferation, cardiacspecific gene expression, and proper patterning of the developing heart.…”
Section: Introductionmentioning
confidence: 99%